CFD simulation of wind-driven upward cross ventilation and its enhancement in long buildings: Impact of single-span versus double-span leeward sawtooth roof and opening ratio. (1st February 2016) - Perén, J.I.; van Hooff, T.; Leite, B.C.C.; Blocken, B.
Abstract: A leeward sawtooth roof building has an inlet opening in the lower level of the windward facade and an upper-level outlet opening near the roof top, in the leeward facade. Leeward sawtooth roof buildings can be applied to efficiently ventilate low-rise buildings. Previous studies of the authors showed that the ventilation potential strongly depends on the roof inclination angle and roof geometry. The current study focuses on the ventilation flow in single-zone elongated low-rise buildings with a single-span versus double-span leeward sawtooth roof and different opening ratios. Straight, concave and convex roof geometries are evaluated. The analysis is performed using 3D steady Reynolds-averaged Navier–Stokes Computational Fluid Dynamics (CFD) simulations with the SST k-ω turbulence model. The computational grid is based on a grid-sensitivity analysis and the simulation results are validated based on Particle Image Velocimetry (PIV) measurements from literature. For the single-span cases, the convex roof results in the highest volume flow rate, which is about 8.8% higher than for the concave roof, and 3.5% higher than the straight roof. A double-span roof performs slightly better than a single-span roof with respect to ventilation flow rates (below 4.2%) in case of a straight or concave roof, but worse in case of a convex roof (−12%). The internal roof geometry near the outlet opening plays an important role in the ventilation of the building. Finally, the inlet-to-outlet opening ratio has an important effect on the volume flow rates, with significantly higher ventilation flow rates for a lower opening ratio. Graphical abstract: Highlights: CFD simulations of natural cross-ventilation flow with 3D steady RANS. Grid-sensitivity analysis and validation with PIV measurements. Influence of single and double-span leeward sawtooth roof geometry on flow rate and indoor velocities. Highest volume flow rates with convex roof geometries. Size and magnitude of underpressure zone in the wake mainly depend of the first-span geometry.